The way of life: John Paul II and the challenge of liberal modernity - Holloway, Carson (Baylor Univ. Press, 2008)
Introduction -- The gospel of life and the culture of death -- Hobbes and the origins of liberal modernity -- Locke's theistic liberalism -- Hume and the morality of sympathy -- The ambiguity of the American founding -- Tocqueville and the moral trajectory of modern democracy -- Conclusion